Scattering Characteristics of Mirror Antennas with Discrete Reflectors - Al-Gawagzeh, Mohammed Yousef; Hendi, Amjad Yousef (Elektronika ir Elektrotechnika, 2008)
On the basis of integral equation for two dimensional models, a numerical analysis of scattering properties of mirror antennas with discrete reflectors is presented with the result of calculation of monosatatic and bistatic scatter characteristics. The influence of geometric parameters and frequency factors on scattering characteristics of mirror antennas with discrete reflectors were analyzed. Ill. 6, bibl. 11 (in English; summaries in English, Russian and Lithuanian).